High-strength and high-conductivity copper-nickel-silicon alloy for lead frame and preparation method thereof

A copper-nickel-silicon alloy with controlled trace elements and multi-stage processing enhances strength and conductivity, addressing the limitations of existing alloys for lead frames in semiconductor components.

CN119220854APending Publication Date: 2024-12-31INSTITUTE OF MATERIALS & INTELLIGENT MANUFACTURING JIANGXI ACADEMY OF SCIENCES
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411312015.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-20
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

Existing copper-nickel-silicon alloys struggle to meet the increasing demands for higher strength and conductivity required by advanced semiconductor components and integrated circuit packaging, particularly in lead frames, due to variations in the effects of trace elements on electrical conductivity and mechanical properties.

Method used

A copper-nickel-silicon alloy with controlled compositions of Co, Mg, and Ag, combined with multi-stage cold working and aging treatments, to optimize the size and distribution of precipitated phases, enhancing the synergistic interaction between precipitates and dislocations.

Benefits of technology

The alloy achieves significantly improved tensile strength, conductivity, and hardness, suitable for large-scale production, meeting the performance requirements of high-end integrated circuit lead frames with a tensile strength of 825MPa and conductivity of 46.17% IACS.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119220854A_ABST
    Figure CN119220854A_ABST
Patent Text Reader

Abstract

The invention discloses a high-strength and high-conductivity copper-nickel-silicon alloy for a lead frame and a preparation method of the high-strength and high-conductivity copper-nickel-silicon alloy. The high-strength and high-conductivity copper-nickel-silicon alloy comprises the following components in percentage by mass: 1.75-1.86 wt% of Ni, 1.02-1.1 wt% of Co, 0.54-0.62 wt% of Si, 0.12-0.13 wt% of Mg, less than or equal to 1.0 wt% of Ag and the balance of Cu. The preparation method comprises the following steps: 1) preparing the raw materials according to the alloy components and the mass percentage content, and carrying out alloy casting by using a vacuum melting furnace; (2) the cast ingot is subjected to solution treatment and then rapidly water-cooled to the room temperature, so that the solid solution state of the alloy is reserved; the method comprises the following steps of (1) carrying out primary cold rolling on a cast ingot, (2) carrying out secondary cold rolling on the cast ingot, (3) carrying out hot rolling on the cast ingot after surface defects of the cast ingot are milled off, (4) carrying out primary cold rolling, annealing for 4 hours at the temperature of 420-440 DEG C, carrying out secondary cold rolling, annealing for 4 hours at the temperature of 310-330 DEG C, carrying out aging treatment until the thickness is 0.2 mm, carrying out tertiary aging treatment at the temperature of 100-400 DEG C for 2-20 hours, and carrying out air cooling to the room temperature. The highest tensile strength of the obtained copper alloy strip is 825 MPa, the highest yield strength is 790 MPa, the highest hardness is 252.9 HV, the highest electric conductivity is 46.17% IACS, and the highest elongation is 3.16%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of metal material preparation and processing, in particular to a high-strength and high-conductivity copper-nickel-silicon alloy for a lead frame and a preparation method thereof. Background Art

[0002] In the field of semiconductor components and integrated circuit packaging, lead frame materials play a key role. As the supporting skeleton, heat dissipation channel and signal transmission path of the chip, the performance requirements of its materials are increasing day by day. With the rapid increase in chip integration, lead frame materials not only need to have high strength to ensure mechanical stability, but also need to have high conductivity to ensure excellent signal transmission and heat dissipation performance. In order to meet these demanding performance requirements, the selection of materials becomes crucial.

[0003] At present, copper-nickel-silicon copper alloys not only have high strength and high conductivity, but also provide excellent thermal stability, corrosion resistance and processing performance, while maintaining good fatigue tolerance, and have become one of the first choices for lead frame materials. Copper-nickel-silicon alloys represented by C70250 have a strength of 600-800MPa and a conductivity of 30%-40%IACS. They are mainly used in elastic components, integrated circuit lead frames and patch electronic devices. However, with the rapid development of science and technology, as well as the needs of integration, lightweight and large-scale integration of electronic products, higher and higher requirements are placed on the strength and conductivity of copper alloys. Existing copper-nickel-silicon alloys are difficult to meet the requirements. Cu-Ni-Si alloy is a typical aging-strengthened alloy. Its excellent performance is mainly attributed to the precipitation of fine and dispersed Ni from the matrix during subsequent heat treatment. 2 Si phase. At the same time, the solute atoms such as Ni and Si in the alloy matrix are consumed during the precipitation process, thereby reducing electron scattering and improving electrical conductivity. On this basis, adding trace elements can further optimize the mechanical properties and electrical conductivity of Cu-Ni-Si alloys, which is an effective way to improve their comprehensive performance. However, although the tensile strength of Cu-Ni-Si alloys can be improved to varying degrees after adding different trace elements, there are still obvious differences in the effects of different trace elements on the electrical conductivity of the alloy. Therefore, according to the purpose of the material, the type and content of certain trace elements should be specifically regulated to obtain a Cu-Ni-Si alloy that meets the requirements of practical applications. Summary of the invention

[0004] The purpose of the present invention is to provide a high-strength and high-conductivity copper-nickel-silicon alloy for lead frames with excellent comprehensive performance. By introducing appropriate amounts of Co, Mg, and Ag elements on the basis of Ni and Si, the alloy is significantly improved in terms of hardness, tensile strength, and conductivity. By controlling the size and distribution of the precipitated phase, the adverse effects of large-particle precipitates on material properties are reduced. In addition, by optimizing the aging treatment conditions, combining the cold rolling process, and utilizing the synergistic effect of multiple alloying elements to strengthen the interaction between precipitates and dislocations, a high-strength and high-conductivity copper-nickel-silicon alloy for lead frames with excellent comprehensive performance is prepared.

[0005] In order to achieve the above object, the present invention adopts the following technical solutions.

[0006] The high-strength and high-conductivity copper-nickel-silicon alloy for a lead frame described in the present invention is characterized in that the components and their mass percentages of the copper alloy strip are: Ni: 1.75wt% to 1.86wt%, Co: 1.02wt% to 1.1wt%, Si: 0.54wt% to 0.62wt%, Mg: 0.12wt% to 0.13wt%, Ag≤1.0wt%, and the balance is Cu.

[0007] Preferably, it is composed of the following mass percentages: Ni: 1.75wt%, Co: 1.02wt%, Si: 0.54wt%, Mg: 0.12wt%, Ag: 0.47wt%, and the balance is Cu.

[0008] Preferably, Ni: 1.78wt%, Co: 1.05wt%, Si: 0.56wt%, Mg: 0.13wt%, Ag: 0.93wt%, and the balance is Cu.

[0009] The method for preparing a high-strength and high-conductivity copper-nickel-silicon alloy for a lead frame described in the present invention comprises the following steps.

[0010] Step 1: Prepare the raw materials according to the alloy composition and mass percentage, and add the raw materials except magnesium into the melting crucible of the vacuum induction melting furnace. The magnesium raw material is placed in a descending copper tube above the melting crucible for secondary feeding in a vacuum environment. The air in the melting furnace is extracted to 1.3-1.4×10 1 Pa, and then introduce argon to maintain the pressure in the furnace at 0.04-0.05MPa. Then turn on the induction heating device of the vacuum induction furnace, increase the temperature, and completely melt the raw materials in the melting crucible into a molten state and keep it for 3-4 minutes. Then lower the copper tube containing magnesium particles to melt it in the crucible, wait for 2-3 minutes, and ensure that all raw materials are fully melted and evenly mixed. Pour the melt into the mold to obtain an ingot, and take it out after cooling with the furnace.

[0011] Step 2, solution treating the ingot at a temperature of 840°C to 860°C, keeping the ingot at this temperature for 5 hours, and then rapidly cooling the ingot to room temperature to retain the solid solution state of the alloy.

[0012] Step 3: After the surface defects of the ingot are removed by milling, the ingot is hot rolled at a temperature of 770°C to 790°C for 30 minutes, and the reduction amount per pass is 30%, and the ingot is hot rolled to 15 mm.

[0013] Step 4, perform the first cold rolling, first cold rolling the thickness from 15mm to 2mm, with a reduction of 20% per pass, and then perform the first aging treatment: annealing at 420℃~440℃ for 4 hours. Then perform the second cold rolling, further cold rolling the thickness to 0.45mm, with a reduction of 10% per pass, and then annealing at 310℃~330℃ for 4 hours for the second aging treatment, and finally cold rolling the thickness to 0.2mm. Finally, the 0.2mm cold-rolled alloy strip is subjected to a third aging treatment at 100°C~400°C for 2h~20h, and air-cooled to room temperature after aging.

[0014] Preferably, the temperature of the solution treatment in step 2 is 850°C and the insulation time is 5 hours.

[0015] Preferably, the hot rolling temperature in step 3 is 780°C and the holding time is 30 minutes.

[0016] Preferably, the first aging treatment in step 4 is performed at a temperature of 430°C for 4 hours; the second aging treatment is performed at a temperature of 320°C for 4 hours; the third aging treatment is performed at a temperature of 320°C for 4 to 6 hours, and air-cooling is performed to room temperature after aging.

[0017] The addition of Co element in the present invention can significantly improve the strength and electrical conductivity of Cu-Ni-Si alloy. This performance improvement is mainly because at the aging temperature, as the Co content increases, the solid solubility of Ni, Co and Si solute atoms decreases, thereby promoting the formation of more precipitated phases. Studies have shown that Co atoms preferentially nucleate at vacancies at the beginning of aging, which helps to reduce the Si content in the Cu matrix and inhibit the slip of mobile dislocations. Although adding a large amount of Co will seriously reduce the electrical conductivity of copper alloys, an appropriate amount of Co element has a positive effect on the properties of the alloy. The fine Co generated by the reaction of Co and Si 2 Si phase is preferentially formed at vacancy defects, which not only promotes Ni 2 The Si phase nucleation also inhibits the Ni 2 The growth of Si phase during the aging process optimizes the comprehensive properties of the alloy.

[0018] The larger atomic radius difference between the Mg element and the Cu element of the present invention helps to improve the recrystallization temperature and high temperature softening ability of the alloy. In addition, studies have shown that the Mg element can inhibit the growth of second phase particles, maintain small and dispersed precipitates in the matrix, thereby improving the strength and electrical conductivity of the alloy. However, when the Mg element is added too much, the excess Mg will be dissolved in the copper matrix, increase electron scattering, and thus reduce the electrical conductivity of the copper alloy. Therefore, adding the Mg element in an appropriate amount is conducive to enhancing the strength and electrical conductivity of the Cu-Ni-Si alloy.

[0019] The addition of a small amount of Ag in the present invention can significantly improve the strength and hardness of the Cu-Ni-Si alloy. Although solid solution strengthening usually increases electron scattering due to lattice distortion caused by solute atoms, thereby reducing the conductivity of the copper alloy, the solid solution of Ag atoms does not significantly reduce the conductivity of the copper alloy. This is because the addition of Ag promotes the 2 Si phase and Co 2 The precipitation of Si phases alleviates the lattice distortion caused by Ni, Co and Si atoms, so it can be considered that Ni 2 Si phase and Co 2 The precipitation of Si phase offsets the negative effect of Ag on conductivity.

[0020] Compared with the prior art, the present invention has the following beneficial effects: The present invention provides a high-strength and high-conductivity Cu-Ni-Si alloy strip for lead frames. Based on the traditional "solid solution-deformation-aging" process, the alloy appropriately increases the silver content, and combines multi-stage cold working and multi-stage aging treatment to regulate the precipitation phase in the alloy, including the size, quantity and morphology of discontinuous precipitation phase and continuous precipitation phase. At the same time, the promotion effect of Co, Mg and Ag elements on the precipitation phase and the hindering effect on dislocation are utilized to achieve the synergistic improvement of the performance of the copper alloy. The Cu-Ni-Si alloy strip finally obtained has significantly improved comprehensive performance, with a tensile strength of 825MPa, an electrical conductivity of 46.17% IACS, and a microhardness of 252.9 HV. The alloy of the present invention is prepared by processes such as melting, solid solution, cold rolling and aging, and the process steps are simple and suitable for large-scale production. The technology is relatively simple, easy to operate and low-cost, and can greatly meet the performance requirements of large-scale high-end integrated circuit lead frame copper alloys. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 The figure is a flow chart for preparing the Cu-Ni-Si alloy of the present invention.

[0022] Figure 2 Hardness curves of the alloy materials prepared in the embodiments of the present invention and the comparative examples under different conditions.

[0023] Figure 3 Conductivity curves of the alloy materials prepared in the embodiments of the present invention and the comparative examples under different conditions. DETAILED DESCRIPTION

[0024] The present invention is further described in detail below in conjunction with specific implementation cases. It is pointed out that the following implementation cases are only used to illustrate the specific implementation methods of the present invention and cannot limit the scope of protection of the present invention. Example 1

[0025] The method for preparing a high-strength and high-conductivity copper-nickel-silicon alloy for a lead frame provided in this embodiment is as follows.

[0026] Step 1: Prepare the raw materials according to the alloy composition and mass percentage of Ni: 1.75wt%, Co: 1.02wt%, Si: 0.54wt%, Mg: 0.12wt%, Ag: 0.47wt%, and the balance is Cu. Add the raw materials except magnesium into the melting crucible of the vacuum induction melting furnace. The magnesium raw material is placed in a descending copper tube above the melting crucible for secondary feeding in a vacuum environment. Draw the air in the melting furnace to 1.4×10 1 Pa, and then argon is introduced to maintain the pressure in the furnace at 0.05MPa. Then the induction heating device of the vacuum induction furnace is turned on, the temperature is increased, and the raw materials in the melting crucible are completely melted to a molten state and maintained for 4 minutes. Then the copper tube containing magnesium particles is lowered to melt it in the crucible, and wait for 3 minutes to ensure that all raw materials are fully melted and evenly mixed. The melt is poured into a mold to obtain an ingot, which is taken out after cooling with the furnace.

[0027] Step 2, solution treatment of the ingot at a temperature of 850° C., keeping the temperature at this temperature for 5 hours, and then rapidly cooling the ingot to room temperature with water to retain the solid solution state of the alloy.

[0028] Step 3: After the surface defects of the ingot are removed by milling, the ingot is hot rolled at a temperature of 780°C for 30 minutes, and the reduction amount per pass is 30%, and the ingot is hot rolled to 15 mm.

[0029] Step 4, the first cold rolling is performed, first the thickness is cold rolled from 15 mm to 2 mm, the reduction amount for each pass is 20%, and then the first aging treatment is performed, specifically annealing at 430 ° C for 4 hours. Then the second cold rolling is performed, the thickness is further cold rolled to 0.45 mm, the reduction amount for each pass is 10%, and then the second aging treatment is performed at 320 ° C for 4 hours, and finally the thickness is cold rolled to 0.2 mm. Finally, the 0.2 mm cold-rolled alloy strip is subjected to a third aging treatment at 320 ° C for 4 hours, and air-cooled to room temperature after aging.

[0030] The copper alloy strip obtained in Example 1 had a tensile strength of 771 MPa, a yield strength of 734 MPa, a hardness of 231.6 HV, a conductivity of 49.72% IACS, and an elongation of 3.12%. Example 2

[0031] Compared with Example 1, the difference is that the third aging treatment is aging at 320° C. for 6 hours. The other preparation steps are the same, and the copper alloy strip in Example 2 has a tensile strength of 768 MPa, a yield strength of 728 MPa, a hardness of 250.3 HV, a conductivity of 49.30% IACS, and an elongation of 5.00%. Example 3

[0032] The method for preparing a high-strength and high-conductivity copper-nickel-silicon alloy for a lead frame provided in this embodiment is as follows.

[0033] Step 1: Prepare the raw materials according to the alloy composition and mass percentage of Ni: 1.78wt%, Co: 1.05wt%, Si: 0.56wt%, Mg: 0.13wt%, Ag: 0.93wt%, and the balance is Cu. Add the raw materials except magnesium into the melting crucible of the vacuum induction melting furnace. The magnesium raw material is placed in a descending copper tube above the melting crucible for secondary feeding in a vacuum environment. Draw the air in the melting furnace to 1.4×10 1 Pa, and then argon is introduced to maintain the pressure in the furnace at 0.04MPa. Then the induction heating device of the vacuum induction furnace is turned on, the temperature is increased, and the raw materials in the melting crucible are completely melted to a molten state and maintained for 3 minutes. Then the copper tube containing magnesium particles is lowered to melt it in the crucible, and wait for 3 minutes to ensure that all raw materials are fully melted and evenly mixed. The melt is poured into a mold to obtain an ingot, which is taken out after cooling with the furnace.

[0034] Step 2, solution treatment of the ingot at a temperature of 850° C., keeping the temperature at this temperature for 5 hours, and then rapidly cooling the ingot to room temperature with water to retain the solid solution state of the alloy.

[0035] Step 3: After the surface defects of the ingot are removed by milling, the ingot is hot rolled at a temperature of 780°C for 30 minutes, and the reduction amount per pass is 30%, and the ingot is hot rolled to 15 mm.

[0036] Step 4, the first cold rolling is performed, first the thickness is cold rolled from 15 mm to 2 mm, the reduction amount for each pass is 20%, and then the first aging treatment is performed, specifically annealing at 430 ° C for 4 hours. Then the second cold rolling is performed, the thickness is further cold rolled to 0.45 mm, the reduction amount for each pass is 10%, and then the second aging treatment is performed at 320 ° C for 4 hours, and finally the thickness is cold rolled to 0.2 mm. Finally, the 0.2 mm cold-rolled alloy strip is subjected to a third aging treatment at 320 ° C for 4 hours, and air-cooled to room temperature after aging.

[0037] The copper alloy strip obtained in Example 2 had a tensile strength of 825 MPa, a yield strength of 790 MPa, a hardness of 252.9 HV, a conductivity of 46.17% IACS, and an elongation of 3.16%. Example 4

[0038] Compared with Example 3, the difference is that the third aging treatment is aging at 320°C for 6 hours. The other preparation steps are the same, and the copper alloy strip in Example 4 has a tensile strength of 799 MPa, a yield strength of 768 MPa, a hardness of 261.6 HV, a conductivity of 44.81% IACS, and an elongation of 2.16%.

[0039] Comparative example 1.

[0040] Compared with Example 1, the difference is the alloy composition and mass percentage: Ni: 1.84wt%, Co: 1.04wt%, Si: 0.59wt%, Mg: 0.12wt%, and the balance is Cu configuration raw material. The remaining preparation steps are the same, and the copper alloy strip in Comparative Example 2 has a tensile strength of 726MPa, a yield strength of 678MPa, a hardness of 217.0HV, a conductivity of 46.47% IACS, and an elongation of 3.80%.

[0041] Comparative example 2.

[0042] Compared with Example 1, the difference is the alloy composition and mass percentage: Ni: 1.80wt%, Co: 1.05wt%, Si: 0.56wt%, Mg: 0.12wt%, Ag: 0.10wt%, and the balance is Cu configuration raw material. The remaining preparation steps are the same, and the copper alloy strip in Comparative Example 1 has a tensile strength of 689MPa, a yield strength of 634MPa, a hardness of 211.0HV, a conductivity of 51.37%IACS, and an elongation of 3.58%.

[0043] Comparison of results of embodiments and comparative examples .

[0044] The present invention adopts a secondary feeding method to add magnesium element. According to ICP component detection, the burnout rate of magnesium element in the smelted ingot is less than 1%. The detection method is in accordance with "GB / T 5121.27-2008 Chemical Analysis Methods for Copper and Copper Alloys Part 27: Inductively Coupled Plasma Atomic Emission Spectrometry".

[0045] From the comparison between Comparative Example 1 and Examples 1 and 2, it can be seen that the addition of an appropriate amount of Ag can significantly improve the strength and hardness of the Cu-Ni-Si alloy. This is because the addition of Ag promotes the 2 Si phase and Co 2 The precipitation of Si phases alleviates the lattice distortion caused by Ni, Co and Si atoms, so it can be considered that Ni 2 Si phase and Co 2 The precipitation of Si phase offsets the negative effect of Ag on conductivity. From the comparison between Examples 1 and 2 and Examples 3 and 4, it can be seen that when the Ag content in the copper alloy of the present invention reaches 0.9wt% or more, although the strength is improved, the conductivity is reduced. This is because excessive Ag is dissolved in the copper matrix, which increases electron scattering and reduces the conductivity of the alloy.

[0046] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the claims of the present invention.

Claims

1. A high-strength and high-conductivity copper-nickel-silicon alloy for a lead frame, characterized in that The alloy components and their mass percentages are as follows: Ni: 1.75wt% to 1.86wt%, Co: 1.02wt% to 1.1wt%, Si: 0.54wt% to 0.62wt%, Mg: 0.12wt% to 0.13wt%, Ag≤1.0wt%, and the balance is Cu.

2. The high-strength and high-conductivity copper-nickel-silicon alloy for lead frame according to claim 1, characterized in that It is composed of the following components and mass percentages: Ni: 1.75wt%, Co: 1.02wt%, Si: 0.54wt%, Mg: 0.12wt%, Ag: 0.47wt%, and the balance is Cu.

3. The high-strength and high-conductivity copper-nickel-silicon alloy for lead frame according to claim 1, characterized in that It is composed of the following components and mass percentages: Ni: 1.78wt%, Co: 1.05wt%, Si: 0.56wt%, Mg: 0.13wt%, Ag: 0.93wt%, and the balance is Cu.

4. The method for preparing the high-strength and high-conductivity copper-nickel-silicon alloy for lead frame according to claim 1, characterized in that The steps include: Step 1: Prepare the raw materials according to the alloy composition and mass percentage, and add the raw materials except magnesium into the melting crucible of the vacuum induction melting furnace; the magnesium raw material is placed in a descending copper tube above the melting crucible for secondary feeding in a vacuum environment; the air in the melting furnace is extracted to 1.3-1.4×10 1 Pa, and then introduce argon gas to maintain the pressure in the furnace at 0.04-0.05MPa; then turn on the induction heating device of the vacuum induction furnace, increase the temperature, completely melt the raw materials in the melting crucible into a molten state and keep it for 3-4 minutes; then lower the copper tube containing magnesium particles to melt it in the crucible, wait for 2-3 minutes to ensure that all raw materials are fully melted and evenly mixed; pour the melt into a mold to obtain an ingot, and take it out after cooling with the furnace; Step 2: performing a solution treatment on the ingot at a temperature of 840°C to 860°C, keeping the temperature at this temperature for 5 hours, and then rapidly cooling the ingot to room temperature to retain the solid solution state of the alloy; Step 3: After the surface defects of the ingot are removed by milling, the ingot is hot rolled; the hot rolling temperature is 770℃~790℃, and the temperature is kept for 30 minutes. During hot rolling, the reduction amount for each pass is 30%, and the ingot is hot rolled to 15mm; Step 4: Perform the first cold rolling, first cold rolling the thickness from 15 mm to 2 mm, with a reduction of 20% per pass, and then perform the first aging treatment: annealing at 420°C to 440°C for 4 hours; then perform the second cold rolling, further cold rolling the thickness to 0.45 mm, with a reduction of 10% per pass, and then annealing at 310°C to 330°C for 4 hours for the second aging treatment, and finally cold rolling the thickness to 0.2 mm; finally, the 0.2 mm cold-rolled alloy strip is subjected to a third aging treatment at 100°C to 400°C for 2 hours to 20 hours, and air-cooled to room temperature after aging.

5. The method for preparing a high-strength and high-conductivity copper-nickel-silicon alloy for a lead frame according to claim 4, characterized in that The temperature of the solution treatment described in step 2 is 850°C and the insulation time is 5 hours.

6. The method for preparing a high-strength and high-conductivity copper-nickel-silicon alloy for a lead frame according to claim 4, characterized in that The hot rolling temperature described in step 3 is 780°C and the holding time is 30 minutes.

7. The method for preparing a high-strength and high-conductivity copper-nickel-silicon alloy for a lead frame according to claim 4, characterized in that the temperature of the first aging treatment in step 4 is 430°C and the time is 4 hours; the temperature of the second aging treatment is 320°C and the time is 4 hours; the temperature of the third aging treatment is 320°C and the time is 4 to 6 hours, and the aging is followed by air cooling to room temperature.

Citation Information

Cited By

  • High-strength and high-conductivity copper alloy lead frame material and preparation method thereof

    CN121472636A

  • Preparation method of ultrahigh-strength conductive copper alloy strip

    CN121874562A